Neurofibromatosis Type 2: Multiple Meningiomatosis and Vestibular Schwannomas on 68Ga-DOTATATE PET/CT. (16th November 2022) - Filizoglu, Nuh; Ozguven, Salih
Abstract: Neurofibromatosis type 2 (NF2) is an autosomal-dominant tumor predisposing syndrome that results from mutations in the NF2 tumor suppressor gene on chromosome 22. The development of bilateral vestibular schwannomas is the characteristic feature of the disease. However, other nervous system tumors, including meningiomas, ependymomas, and schwannomas, can be seen frequently. Herein, we present 68 Ga-DOTATATE PET/CT findings of 2 siblings with NF2.